Trace elements in the environment - Prasad, M.N.V. (Taylor & Francis, 2006)
New analytical techniques have enhanced current understanding of the behavior of trace and ultratrace elements in the biogeochemical cycling, chemical speciation, bioavailability, bioaccumulation, and as applied to the phytoremediation of contaminated soils. Addressing worldwide regulatory, scientific, and environmental issues, Trace Elements in the Environment explores these frontiers, including biotechnological aspects of metal-binding proteins and peptides and phytoremediation strategies using trees, grasses, crop plants, aquatics, and risks to ecological and human health. Discussing trace elements in the holistic environment, this book covers advances in state-of-the-art analytical techniques, molecular biotechology, and contemporary biotechnology that enhances knowledge of the behavior of trace elements in the biogeosphere and at the cellular and molecular level.